Bulgaria and the Ukrainian crisis: national interests and political institutions - Cholakov, Petar G. (Sociološki pregled, 2021)
The Ukrainian crisis is an arena of geopolitical conflict in which the interests of Russia, NATO and the EU intertwine. It is in this context that the behaviour of Bulgarian political institutions has to be analyzed. In the first section, I explore the reactions and positions of the Bulgarian governments, the main political parties and the presidential institution towards the Ukrainian crisis. In the second part, I highlight the tools used by Russia in order to influence Bulgarian political institutions and processes. The third section traces the measures undertaken by the United States and the EU to neutralize Russia’s clout. I defend the view that Sofia needs to be more consistent in fulfilling its commitments to NATO and the EU.
Keywords: Bulgaria and the Ukrainian crisis; Russia and political parties in Bulgaria (2013–2020); Russian energy projects and Bulgarian politics